PPUPIK PRODUK ABON TUNA UNTUK MENINGKATKAN PENDAPATAN DI LABORATORIUM AGROBISNIS PERIKANAN - Fakhriyyah, Sitti (Jurnal Abdimas Gorontalo (JAG), 2023)
PPUPIK is a Campus Intellectual Product Business Development Program. This program is one of the service schemes granted by Hasanuddin University for its lecturers. This scheme is the output of products or services that can generate income for the laboratory. One of the products is shredded tuna. This product is produced for sale so as to earn campus income. Where the Hasanuddin University campus is one of the Legal Entity State Universities (PTNBH). This tuna shredded product is produced in the Fisheries Agribusiness Laboratory. The short-term goal is to train students to be entrepreneurial and the long-term goal is to earn income. The method used is a demonstration of making shredded tuna, then packaged and marketed. This activity involved 4 students accompanied by 4 lecturers. The results of the demonstration from 5 kg of tuna fish are only 4.7 kg of shredded tuna. Where shrinkage as much as 300 grams. There are 2 packages of shredded production, namely plastic packaging and box packaging containing 100 grams each.